2020
DOI: 10.2147/rrtm.s274518
|View full text |Cite
|
Sign up to set email alerts
|

<p>Current Understanding of Immunity Against Schistosomiasis: Impact on Vaccine and Drug Development</p>

Abstract: Schistosomiasis is a neglected tropical disease inflicting significant morbidity in humans worldwide. The disease is caused by infections with a parasitic trematode belonging to the genus Schistosoma . Over 250 million people are currently infected globally, with an estimated disability-adjusted life-years of 1.9 million attributed to the disease. Current understanding, based on several immunological studies using experimental and human models of schistosomiasis, reveals that complex imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 106 publications
1
32
0
1
Order By: Relevance
“…Most importantly, the multi-stage nature of schistosomes, transforming from cercariae to Schistosomula, adult worms and ultimately eggs, involves complex antigenic switches which are life-stage specific, but can also be present across life stages. In addition, the induction of IgE responses, associated risk of allergic reactions and the potential of aggravating granulomas and fibrosis by egg-mediated responses ( 10 ) makes schistosomiasis vaccine development complex.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most importantly, the multi-stage nature of schistosomes, transforming from cercariae to Schistosomula, adult worms and ultimately eggs, involves complex antigenic switches which are life-stage specific, but can also be present across life stages. In addition, the induction of IgE responses, associated risk of allergic reactions and the potential of aggravating granulomas and fibrosis by egg-mediated responses ( 10 ) makes schistosomiasis vaccine development complex.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally acquired immunity is characterized by a broadening of antibody repertoire and a switch from predominantly egg-specific IgG1, IgG2, and IgM antibodies in infancy to a protective larval and adult worm-specific IgE antibodies toward adulthood and increasing duration of exposure ( 43 , 47 49 ). IgE response, elicited after repeated exposure and or PZQ treatment is associated with protection (though not exclusively) in endemic populations ( 10 ). Natural or PZQ-driven death of adult worms releases parasite antigens from migrating larvae and this induces IgE response ( 50 ) which mediates antibody-dependent-cellular-cytoxicity (ADCC) killing of more parasites ( 31 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While certain helminth infections could reduce the severity of COVID‐19, other helminths at different life cycles can also exacerbate immunopathology. The immune response in acute stage of schistosomiasis is mostly associated with a Th1 type immune response which is dramatically shifted to a Th2 type cytokine expression when the females start to lay eggs 78 …”
Section: Immunomodulatory Effects Of Helminth; the Era Of Sars‐cov‐2 ...mentioning
confidence: 99%
“…Scientists worldwide have made tremendous efforts to produce vaccines that aimed to protect from COVID‐19. Many vaccine strategies for SARS‐CoV‐2 have demonstrated efficacy in clinical trials, including mRNA encoding of the SARS‐CoV‐2 spike glycoprotein, recombinant spike protein, adenovirus vector expressing the surface glycoprotein, as well as delivery of whole inactivated virus as reviewed from 80 . As of October 27, 2021, there are 155 vaccine candidates, 485 vaccine trials ongoing, and 42 of these vaccines have entered phase III clinical trials with 23 approved vaccines 81 and of these about 12 (Table 3) have reported efficacy in the peer‐reviewed literature.…”
Section: Implications Of Helminth Infections In Covid‐19 Vaccine Resp...mentioning
confidence: 99%